Location-Allocation of Police Vehicles under a Multi-period Perspective - de Lucena, Amarildo J. F.; Bocanegra, Silvana; Gorgônio, Flavius L. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
The aim of this work is to propose a decision support framework to contribute to the allocation of police vehicles in urban centres. We are using a multi-period facility location mathematical model to decide where and when to locate police vehicles in order to minimize the total cost (travel time to attend the calls) over the planning horizon. This system is building using the AIMMS software for modelling and solving the mathematical model. The forecasting of call demands was done using the Monte Carlo simulation and the maps of the studied urban centre were integrated within the AIMMS. A case of study in Recife-PE city was used to evaluate the applicability of the proposed approach. The decision maker can easily operate a graphical interface for changing the maximum number of vehicles that can be operating in each period of time and evaluate the impacts on the allocation and the total cost.